2012
DOI: 10.1037/a0026560
|View full text |Cite
|
Sign up to set email alerts
|

Attention and working memory capacity: Insights from blocking, highlighting, and knowledge restructuring.

Abstract: The concept of attention is central to theorizing in learning as well as in working memory. However, research to date has yet to establish how attention as construed in one domain maps onto the other. We investigate two manifestations of attention in category- and cue-learning to examine whether they might provide common ground between learning and working memory. Experiment 1 examined blocking and highlighting effects in an associative learning paradigm, which are widely thought to be attentionally mediated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
73
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(89 citation statements)
references
References 102 publications
(224 reference statements)
16
73
0
Order By: Relevance
“…Despite the required attentional control, the use of rule strategies was not associated with higher WMC. These results are consistent with recent work by Sewell and Lewandowsky (2011a) who examined blocking and highlighting in a category-learning task. In blocking and highlighting, early learning between cues and outcomes occludes subsequent learning of associations between new cues and the same outcomes (Kamin, 1969;Medin & Edelson, 1988; and see also Kruschke, 2005).…”
Section: Wmc and Attention In Categorizationsupporting
confidence: 95%
“…Despite the required attentional control, the use of rule strategies was not associated with higher WMC. These results are consistent with recent work by Sewell and Lewandowsky (2011a) who examined blocking and highlighting in a category-learning task. In blocking and highlighting, early learning between cues and outcomes occludes subsequent learning of associations between new cues and the same outcomes (Kamin, 1969;Medin & Edelson, 1988; and see also Kruschke, 2005).…”
Section: Wmc and Attention In Categorizationsupporting
confidence: 95%
“…A number of theoretical accounts of category learning suggest that the acquisition of new categories is a complex activity that may involve a series of specific cognitive abilities or processes (e.g., Ashby & Maddox, 2011;Ashby & O'Brien, 2005). Several recent studies have indicated that working memory plays an important part in category learning (e.g., Craig & Lewandowsky, 2012DeCaro, Carlson, Thomas, & Beilock, 2009;DeCaro, Thomas, & Beilock, 2008;Erickson, 2008;Lewandowsky, 2011;Lewandowsky, Yang, Newell, & Kalish, 2012;Sewell & Lewandowsky, 2012). However, those studies were complicated by the complexity of working memory which is not a unitary construct but consists of multiple components or processes (Baddeley, 1986;Miyake et al, 2000), and it remains unclear which specific processes are involved in category learning.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity associated with the course of acquiring new categories raises the question of what key processes contribute to the performance in category learning. A few empirical studies have already been conducted to identify the key processes by considering a range of cognitive abilities and processes such as attention (Sewell & Lewandowsky, 2012), semantic memory (Ashby & O'Brien, 2005), and working memory (Craig & Lewandowsky, 2012, among which working memory has received the most attention.…”
Section: Introductionmentioning
confidence: 99%
“…Among other mechanisms, an intriguing possibility is that changes in attention to cues and contexts can facilitate new learning and protect previous knowledge from interference. A popular effect known as highlighting provides an excellent example to understand how this process works (see Kruschke 2009;Sewell and Lewandowsky 2012). In a typical highlighting experiment, participants are first exposed to a series of exemplars with two different features, A and B, that have to be classified as members of category 1.…”
mentioning
confidence: 99%